Developing a master of science in health research ethics program in Northern Nigeria: a needs assessment - Caitlin Bieniek; Fatimah I. Tsiga-Ahmed; Aishatu L. Adamu; Usman J. Wudil; C. William Wester; Zubairu Iliyasu; Muktar H. Aliyu; Elisa J. Gordon; Elizabeth S. Rose (BMC Medical Ethics)
Abstract Background Nigeria is an emerging hub of biomedical research, requiring additional trained bioethicists for ethical oversight of research studies. There are currently two graduate-level health research ethics programs in Nigeria. However, both are in the southern part of the country and no such training programs exist in the north. Strengthening the health research ethics skills and knowledge of Nigerian researchers across the country is necessary given the growing genetics research infrastructure. Methods To inform the creation of a Master of Science in Health Research Ethics program in northern Nigeria, we conducted a needs assessment comprised of semi-structured interviews with nine Nigerian bioethics experts. We used the Interpretative Phenomenological Analysis (IPA) method to analyze interview transcriptions. Two authors independently read and coded each respondent’s transcript to identify emergent themes that represented each respondent’s answers. Within these overarching themes, the data points were grouped into subthemes. Results Four primary themes emerged with ten subthemes. Respondents believed that the program can fill a gap and strengthen capacity in health research ethics. They emphasized that the curriculum should be developed with an interdisciplinary lens and locally contextualized, and that students should be taught how to think critically through ethical scenarios. Respondents stressed that program leaders should recruit faculty and students locally who have the bandwidth to participate in the program. Finally, respondents noted the program should have university support to be sustainable. Conclusion Our findings will guide the creation of a master’s degree program that aims to build capacity in health research ethics in northern Nigeria and enhance the country’s growing prominence in global biomedical research. Through our needs assessment, we identified structural and content factors that can guide us in leveraging the strengths of the local institution and leaders in health research ethics while mitigating challenges in establishing this program.